If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1 = 6x + 5 Reorder the terms: -1 + 8x = 6x + 5 Reorder the terms: -1 + 8x = 5 + 6x Solving -1 + 8x = 5 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -1 + 8x + -6x = 5 + 6x + -6x Combine like terms: 8x + -6x = 2x -1 + 2x = 5 + 6x + -6x Combine like terms: 6x + -6x = 0 -1 + 2x = 5 + 0 -1 + 2x = 5 Add '1' to each side of the equation. -1 + 1 + 2x = 5 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = 5 + 1 2x = 5 + 1 Combine like terms: 5 + 1 = 6 2x = 6 Divide each side by '2'. x = 3 Simplifying x = 3
| 184-2x=43x+19 | | 20x+12+17x+4=90 | | 9x+6=5x+18 | | 9-10x=109-38x | | 19x-3x= | | -27-8x=8x+21 | | 3x+11=-28-10x | | -6t-11q-16t= | | X-17=-19 | | 2.5-2x=-10.5 | | 7x+25=3x+41 | | 181-6x=5x+16 | | 7x+16=4x+49 | | 12x-(-6)=18+11X | | 5x+2y=11 | | 137-5x=40x+22 | | 5-9x=90-44x | | 12y+1=9y+18 | | 0.2(5x-1)+0.2x=3.1(x+2) | | 3y-1+y+15=6y+20-4y | | 3x+9=-81-7x | | 3x+8=x+24 | | 85-4x=2x+7 | | x^4=-5 | | 63-4x=10x+21 | | x^4=5 | | 3+10x=66+x | | 2x-3=12x-43 | | 5x^2-14x=-8 | | 2x+19=11x-62 | | 3x^2+10x-7= | | 3x+46=6x+10 |